1992
DOI: 10.1063/1.107162
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and formation mechanism of chemically etched silicon

Abstract: Room-temperature photoluminescence (PL) from Si chemically etched (CE) in HF-HNO3-based solution has been observed. Scanning electron microscopy reveals that the etched Si has a surface morphology similar to that of luminescent porous Si fabricated by conventional anodization. PL spectra show an order of magnitude smaller luminescent intensity and a shorter wavelength intensity peak for CE Si. A CE Si thickness limitation was observed. The formation of CE Si can be readily explained by a local anodization mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(72 citation statements)
references
References 13 publications
4
67
0
1
Order By: Relevance
“…As known HNO 3 is an oxidizing agent for Si and the formation of the (NH 4 ) 2 SiF 6 requires reduction of nitrogen. By referring to the mechanisms proposed in the case of stain-etching [4] we can write:…”
Section: Methodsmentioning
confidence: 99%
“…As known HNO 3 is an oxidizing agent for Si and the formation of the (NH 4 ) 2 SiF 6 requires reduction of nitrogen. By referring to the mechanisms proposed in the case of stain-etching [4] we can write:…”
Section: Methodsmentioning
confidence: 99%
“…3͑a͒ and 3͑c͔͒ exhibit a broad emission peaking at ϳ2.0− 2.1 eV, which is typically observed in stain etched PSi samples in HF/ HNO 3 -based solutions. 3,[9][10][11][12][13][14] The stain etched sample in the 47 wt % solution ͓Fig. 3͑d͔͒ also exhibits a broad peak at ϳ2 eV.…”
Section: A Photoluminescencementioning
confidence: 99%
“…However, a careful comparison with a micrograph of a conventionally anodized sample revealed that the surface morphologies are similar, suggesting that the stain etching can produce a lightemitting PSi layer on the surface. 4,6 Furthermore, the AFM and TEM of conventionally anodized, laterally anodized, and stain-etched silicon layers showed that these porous layers have a "fractal-type" surface morphology. 23 The schematic energy band configurations in the vicinity of the surface of a n-type silicon before and after photoetching in 1 M NaF solution are shown in Fig.…”
Section: Fig 2 Large-scale Afm Images Ofmentioning
confidence: 99%